진행성 비소세포폐암 환자에서 Gefitinib와 Erlotinib의 비교 - 이진화; Jin Hwa Lee; 이경은; Kyoung Eun Lee; 류연주; Yon Ju Ryu; 천은미; Eun Mi Chun; 장중현; Jung Hyun Chang (Tuberculosis and respiratory diseases, 2009)
연구배경: 표피성장인자수용체(epidermal growth factor receptor, EGFR) 티로신 활성효소 억제제(tyrosine kinase inhibitor, TKI)는 진행성 비소세포폐암의 새로운 치료제이다. 몇몇 연구 결과 gefitinib와 erlotinib에 대한 반응률과 반응 예측인자에 차이가 있을 가능성을 제시하였다. 저자들은 한국인 진행성 비소세포폐암에서 gefitinib와 erlotinib의 효과 및 독성을 비교하고 각 약제에 대해 서로 다른 반응 예측인자가 있는지 평가하였다. 방법: 2003년 7월부터 2009년 2월까지 이화여자대학교부속병원에서 진행성 비소세포폐암으로 gefitinib 또는 erlotinib로 치료 받은 환자들의 임상정보를 수집하였다. 중앙 생존기간은 Kaplan-Meier법으로 계산하였다. 결과: 대상 환자는 총 86명이었다(gefitinib군 52명 대 erlotinib군 34명). 나이의 중앙값은 64세였고 53명(62%)이 남자였다. 86명 중 83명에서 반응평가가 가능했으며, 83명 중 35명이 반응을 보였고 12명이 안정성 질환이었으며 36명이 진행성 질환으로, 치료 반응률이 42%였고 질병 조절률이 57%였다. 중앙 추적관찰기간 502일 동안, 진행까지의 중앙기간은 129일이었으며 중앙 생존기간은 259일이었다. 치료 반응률(gefitinib 44% 대 erlotinib 39%, p=0.678), 중앙 생존기간(gefitinib 301일 대 erlotinib 202일, p=0.151) 및 병의 진행까지 기간의 중앙값(gefitinib 136일 대 erlotinib 92일, p=0.672)은 두 군 사이에 차이가 없었다. 두 약제는 비슷한 독성을 보였다. Cox 회귀모형을 이용한 다변수분석에서 선암이 생존과 관련된 독립적인 예후인자였다(상대위험도: 0.487, 95% 신뢰구간: 0.292∼0.811, p=0.006). 아집단 분석 결과 두 약제에 대한 서로 다른 반응 예측인자는 없었다. 결론: Gefitinib와 erlotinib 사이에 반응률, 생존기간, 진행까지의 기간 및 독성에 차이는 없었다. 각 약제에 대한 특이적인 반응 예측인자도 없었다. Background: The epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs), became an attractive therapeutic option for advanced non-small-cell lung cancer (NSCLC). Several studies suggested that there might be some different efficacy or response predictors between gefitinib and erlotinib. We compared the efficacy and toxicity of gefitinib and erlotinib in Korean patients with advanced NSCLC and evaluated specific predictors of response for both gefitinib and erlotinib. Methods: We collected the clinical information on patients with advanced NSCLC, who were treated with gefitinib or erlotinib at the Ewha Womans University Hospital, between July 2003 and February 2009. Median survival times were calculated using the Kaplan-Meier method. Results: Eighty-six patients (52 gefitinib vs. 34 erlotinib) were enrolled. Patient median age was 64 years; 53 (62%) subjects were male. Out of the 86 patients treated, 83 received response evaluation. Of the 83 patients, 35 achieved a response and 12 experienced stable disease while 36 experienced progressive disease, resulting in a response rate of 42% and a disease control rate of 57%. After a median follow-up of 502 days, the median progression-free and overall survival time was 129 and 259 days, respectively. Comparing patients by treatment (gefitinib vs erlotinib), there were no significant differences in the overall response rate (44% vs. 39%, p=0.678), median survival time (301 days vs. 202 days, p=0.151), or time to progression (136 days vs. 92 days, p=0.672). Both EGFR-TKIs showed similar toxicity. In a multivariate analysis using Cox regression model, adenocarcinoma was an independent predictor of survival (p=0.006; hazard ratio [HR], 0.487; 95% confidence interval [CI], 0.292-0.811). Analyses of subgroups did not show any difference in response predictors between gefitinib and erlotinib. Conclusion: Comparing gefitinib to erlotinib, there were no differences in the response rate, overall survival, progression-free survival, or toxicity. No specific predictor of response to each EGFR-TKI was identified.